The Impact of Zakat, Agricultural Output, and Poverty on Indonesia’s Food Security - Salsabila, Adzkia Amatullah; Nurasyiah, Aas; Firmansyah, Firmansyah (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: The originality of this research lies in integrating zakat as an Islamic financial instrument into the analysis of food security in Indonesia, a topic that has rarely been explored. Furthermore, it links the concept of maqashid sharia with the Sustainable Development Goal 2 (Zero Hunger), thus offering a novel contribution both theoretically and practically to the food security literature. Research Purpose: This study aims to assess the likelihood of food security across Indonesian provinces and investigate the role of zakat solutions. Research Methods: Employing a quantitative methodology, panel data on zakat utilization, agricultural output, and poverty levels from 34 Indonesian provinces (2013-2022) were analyzed using EViews 9. Empirical Results: The findings reveal that agricultural output and zakat utilization have a positive and significant impact on food security, whereas poverty has a negative effect. Implications: More effective policies are necessary to manage zakat utilization, enhance food production, and alleviate poverty, thereby ensuring Indonesia has a more stable and sufficient food supply for all. JEL Classification: Q18, I32, O13, Z12 How to Cite:Salsabila, A. A., Nurasyiah, A., & Firmansyah. (2025). The Impact of Zakat, Agricultural Output, and Poverty on Indonesia’s Food Security. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 549-562. https://doi.org/10.15408/sjie.v14i2.44738.